Identifying critical work-related characteristics in police roles: A comparative analysis using the O*NET framework - Tedeholm, Peter G (International journal of police science & management, 2025)
Policing roles require specific work-related characteristics (WRCs) critical for effective performance. This study identifies key WRCs for various roles within the Swedish Police—patrol officers, criminal investigators, Special Weapons and Tactics (SWAT) Teams, police chiefs, and negotiators—by analyzing data from 425 active-duty officers (30% response rate). We use the Occupational Information Network (O*NET) framework to assess WRCs in five domains and subsequently compare the identified profiles with the average U.S. workforce and U.S. law enforcement roles. Our findings indicate distinct differences in the WRC profiles required across various roles within the Swedish Police. Frontline roles, such as patrol officers and SWAT unit members, particularly emphasize physical strength, situational awareness, and social skills. At the same time, roles like negotiators and investigators show a higher demand for cognitive abilities and advanced interpersonal competencies. By comparing Swedish police roles with the general U.S. labor market and specific U.S. police functions, our results illustrate how sociocultural factors and organizational structures distinctly shape job demands. This highlights the importance of customizing and regularly updating work analyses to reflect rapid societal and technological changes, ensuring that recruitment, selection, and training processes align with current and future policing demands across national contexts.